HLA Class II tetramers reveal tissue-specific regulatory T cells that suppress T-cell responses in breast carcinoma patients - Schmidt, Hans-Henning; Ge, Yingzi; Hartmann, Felix J.; Conrad, Heinke; Klug, Felix; Nittel, Sina; Bernhard, Helga; Domschke, Christoph; Schütz, Florian; Sohn, Christof; Beckhove, Philipp (OncoImmunology, 2013)
Regulatory T cells (Tregs) play an important role in controlling antitumor T-cell responses and hence represent a considerable obstacle for cancer immunotherapy. The abundance of specific Treg populations in cancer patients has been poorly analyzed so far. Here, we demonstrate that in breast cancer patients, Tregs often control spontaneous effector memory T-cell responses against mammaglobin, a common breast tissue-associated antigen that is overexpressed by breast carcinoma. Using functional assays, we identified a HLA-DRB1*04:01- and HLA-DRB1*07:01-restricted epitope of mammaglobin (mam34-48) that was frequently recognized by Tregs isolated from breast cancer patients. Using mam34-48-labeled HLA Class II tetramers, we quantified mammaglobin-specific Tregs and CD4+ conventional T (Tcon) cells in breast carcinoma patients as well as in healthy individuals. Both mammaglobin-specific Tregs and Tcon cells were expanded in breast cancer patients, each constituting approximately 0.2% of their respective cell subpopulations. Conversely, mammaglobin-specific Tregs and CD4+ Tcon cells were rare in healthy individuals (0.07%). Thus, we provide here for the first time evidence supporting the expansion of breast tissue-specific Tregs and CD4+ Tcon cells in breast cancer patients. In addition, we substantiate the potential implications of breast tissue-specific Tregs in the suppression of antitumor immune responses in breast cancer patients. The HLA Class II tetramers used in this study may constitute a valuable tool to elucidate the role of antigen-specific Tregs in breast cancer immunity and to monitor breast cancer-specific CD4+ T cells.
Gesehen am 05.07.2021